Morphological description and DNA barcoding of some Diamesinae (Diptera, Chironomidae) from the Severnaya Zemlya Archipelago and the Vaigach Island (Russian Arctic) - Krasheninnikov, Andrey B.; Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Gavrilo, Maria V.; Vshivkova, Kristina A. (Zootaxa, 2020)
Chironomids of the Diamesinae subfamily from the Russian Arctic were studied using both morphological characters and molecular data. Adult males of Diamesa urvantsevi sp. nov., D. amplexivirilia Hansen, Arctodiamesa appendiculata (Lundström) from Severnaya Zemlya Archipelago and D. arctica (Boheman), Pseudokiefferiella sp. from Vaigach Island were described, redescribed, annotated and figured. A reference 658 bp barcode sequence from a fragment of the mitochondrial gene cytochrome oxidase I (COI) was used as a tool for species delimitation. For D. arctica (Boheman) and Pseudokiefferiella sp. close DNA barcodes from Norway were performed, which allowed to relate these specimens to the described species. Comparisons with corresponding regions of COI between each described species and close related congeneric species produced K2P genetic distances of 0.11–0.16, values well associated with interspecific variation. Phylogenetic relationships for genera Arctodiamesa Makarchenko and Pseudokiefferiella Zavřel were reconstructed for the first time.